2011
DOI: 10.4314/as.v9i3.65752
|View full text |Cite
|
Sign up to set email alerts
|

Performance and survival of hybrid catfish (hetero x clarias) fed with whole cassava root meal as a replacement for maize

Abstract: This trial was conducted to assess the possibility of replacing maize (Zea mays L) with varying levels of whole cassava (Manihot esculent crantz) root meal (WCRM) in the diet of hybrid catfish (Heterobranchus, bidorsalis x Clarias gariepinus). The effect of replacement on growth variables and nutrient utilization of the WCRM as a replacement for maize were also determined. Four practical diets with varying replacement levels of maize at 0 (A o), 33 (B 33), 66(C 66), and 100% (D 100) were formulated and fed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…However, the parameters were within the appropriate ranges for the catfish culture. Other studies also found and recommend that every growth rate is related to the water quality of the rearing containers (Adeniji and Ovie, 1990;Owhonda et al, 2007;Abu et al, 2010). This study result shows the larvae during first feeding days have good condition, and applying different type of feeds doesn't influence water quality.…”
Section: Water Quality In Relation With Growth Of Larvaesupporting
confidence: 57%
“…However, the parameters were within the appropriate ranges for the catfish culture. Other studies also found and recommend that every growth rate is related to the water quality of the rearing containers (Adeniji and Ovie, 1990;Owhonda et al, 2007;Abu et al, 2010). This study result shows the larvae during first feeding days have good condition, and applying different type of feeds doesn't influence water quality.…”
Section: Water Quality In Relation With Growth Of Larvaesupporting
confidence: 57%
“…Studies on the use of cassava meal in fish feed [48 -50] indicate that cassava can replace the conventional energy feed ingredients such as maize, broken rice and sorghum, which are co mmon ly used in animal d iet in most parts of Africa [51]. Cassava has been successfully used to replace maize in Clarias gariepinus fingerlings -50% replacement [3]; C. garieipinus advanced fry [52] and hybrid catfish (Hetero X Clarias) -66% rep lacement [53]. Inclusion of whole cassava root meal in the diet of fish enhanced growth and survival.…”
Section: Use Of Cassava In Diets For Fishmentioning
confidence: 99%
“…Talthawan et al [28] pointed out that amylopectin is responsible for easy digestion in cassava. For instance, Olurin et al [8] has substituted up to 50 % of corn with cassava starch in fingerlings; Olukunle [30]) replaced corn starch with sweet potato peels and whole root in fry Clarias species while Abu et al [16] was able to replace corn starch with cassava starch up to 66 % with favourable results.…”
Section: Discussionmentioning
confidence: 99%
“…This is coupled to the fact that its production is dwindling [3]. Several attempts have been made to replace or supplement the maize component of fish feed with cheaper non-conventional energy sources;; [2,3,5,6,11,16,17]; Maize offal is component after the starch concentrate. In many occasions, the offal is regarded as a waste component of the maize.…”
Section: Introductionmentioning
confidence: 99%